Edukasi Urgensi Foot Care sebagai Prevensi Risiko Luka Kaki Diabetic di Wilayah Kerja Puskesmas Tamalanrea Jaya Kota Makassar - Rahman, Framita; Gaffar, Indra; Sabriyati, Wa Ode Nur Isnah; Rini, Ita; Rahmaniar, Andi; Natsir, Muh Fajaruddin; Fajar, Rachmat; Ramadhani, Wafiq Aulia; Syukur, Azzahra Marsya; Harisa, Akbar; Yodang, Yodang (Universitas Baiturrahim, 2024)
The Tamalanrea Jaya Community Health Center has a total of 393 DM sufferers in 2022 with 152 male sufferers and 241 female sufferers. The solution offered is to provide guidance regarding the risk of diabetic foot wounds through educational outreach and counseling. The aim of the guidance is to provide information to the community in the Tamalanrea Jaya Community Health Center working area with diabetes melitus (DM) in adults and the elderly regarding the understanding, causes and prevention of diabetic foot wounds. This activity was held on September 19, 2023, with 29 participants in the community service outreach program. The inclusion criteria were people with diabetes mellitus in the working area of Tamalanrea Jaya Community Health Center in Makassar City. .The results of this activity showed that the majority of respondents (58.6%) suffered from DM for the first time at the age of 30-50 years with the average age when they first suffered from DM being 49 years, the period when most suffered from DM (44.8%) was more from 3 years and most respondents (48.3%) followed the Prolanis program for more than 3 years. And from this activity, it was found that there was an increase in knowledge after the counseling and presentation was carried out and participants were able to spread it well and correctly according to the steps that had been directed by the service team.